METHODS OF PROMOTION OF HOTEL SERVICES WITH REGARD TO TRENDS OF DEVELOPMENT OF HOTEL BUSINESS - D. Milova (Вестник университета, 2018)
With the development of the hotel business, managers must take into account the peculiarities of the promotion of accommodation facilities. It is expedient with the purpose of revealing of the further tendencies of development of hotels to be guided by preferences of young travelers. The article shows that most people prefer to book hotel services through online agencies, but the segment that book hotels directly is also very significant. Therefore, in order to increase the amount of reservation directly to hotels, it makes sense to resort to the policy of forming long-term relationships with lodgers: sending to personalized e-mails, forming a base of the preferences for regular customers, collecting customer feedback on the site, promoting additional services in dispatch and letters of welcome, etc. Further trends in the development of the hotel business in the world are revealed